2021
DOI: 10.1145/3476057
|View full text |Cite
|
Sign up to set email alerts
|

Do Platform Migrations Compromise Content Moderation? Evidence from r/The_Donald and r/Incels

Abstract: When toxic online communities on mainstream platforms face moderation measures, such as bans, they may migrate to other platforms with laxer policies or set up their own dedicated websites. Previous work suggests that within mainstream platforms, community-level moderation is effective in mitigating the harm caused by the moderated communities. It is, however, unclear whether these results also hold when considering the broader Web ecosystem. Do toxic communities continue to grow in terms of their user base an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 14 publications
11
90
0
Order By: Relevance
“…The majority of past work on bans of harmful communities on Reddit only examined one or two subreddits, often chosen due to notoriety (Hazel Kwon and Shao, 2020;Chandrasekharan et al, 2017;Saleem and Ruths, 2018;Ribeiro et al, 2020a;Habib et al, 2019;Thomas et al, 2021). Many of these studies focused on the average change in behavior across users and did not consider the factors which may drive inter-individual differences in behavior following a ban (Chandrasekharan et al, 2017;Saleem and Ruths, 2018;Habib et al, 2019).…”
Section: Previous Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of past work on bans of harmful communities on Reddit only examined one or two subreddits, often chosen due to notoriety (Hazel Kwon and Shao, 2020;Chandrasekharan et al, 2017;Saleem and Ruths, 2018;Ribeiro et al, 2020a;Habib et al, 2019;Thomas et al, 2021). Many of these studies focused on the average change in behavior across users and did not consider the factors which may drive inter-individual differences in behavior following a ban (Chandrasekharan et al, 2017;Saleem and Ruths, 2018;Habib et al, 2019).…”
Section: Previous Workmentioning
confidence: 99%
“…Different users may respond differently to subreddit bans based on their level of overall activity or community engagement. For example, Ribeiro et al (2020a) found that users that were more active on Reddit prior to a subreddit ban were more likely to migrate to a different platform following a ban. A user's activity levels prior to a ban also impacted whether activity levels increased or decreased upon migrating to a different platform (Ribeiro et al, 2020a).…”
Section: Previous Workmentioning
confidence: 99%
See 3 more Smart Citations